Adverse drug events observed in patients with type 2 diabetes mellitus treated with 100 mg versus 300 mg canagliflozin: a systematic review and meta-analysis of published randomized controlled trials - Pravesh Kumar Bundhun; Girish Janoo; Feng Huang (BMC, 2017)
Abstract Background Nowadays, canagliflozin monotherapy, or in combination with other oral hypoglycemic agents (OHAs), is often administered in patients who are treated for type 2 diabetes mellitus (T2DM). Therefore, we aimed to systematically compare the adverse drugs events (AEs) which were associated with 100 mg versus 300 mg canagliflozin respectively, using a large number of randomized patients with T2DM which were obtained from published trials. Methods Randomized controlled trials (RCTs) comparing 100 mg versus 300 mg canagliflozin in patients who were treated for T2DM were searched from electronic databases. AEs reported during a follow up period ranging from 12 to 104 weeks were considered as the clinical endpoints in this analysis. We calculated odds ratios (OR) with 95% confidence intervals (CIs) and the analyses were carried out by RevMan 5 · 3 software. Results Ten trials involving a total number of 5394 patients (2604 patients who were treated with 100 mg canagliflozin and 2790 patients who were treated with 300 mg canagliflozin) were included. The current results showed that serious AEs were not significantly higher in patients who were treated by 300 mg canagliflozin, with OR: 1.01, 95% CI: 0.79-1.29; P = 0.93. Also, a similar rate of death was observed in patients who were treated by either 100 or 300 mg canagliflozin with OR: 1.13, 95% CI: 0.43-2.94; P = 0.80. Urinary tract infections, postural dizziness and hypoglycemia were also similarly manifested, with OR: 0.93, 95% CI: 0.70-1.23; P = 0.61, OR: 1.51, 95% CI: 0.42-5.37; P = 0.53 and OR: 0.96, 95% CI: 0.81-1.13; P = 0.60 respectively. However, drug discontinuation due to AEs significantly favored 100 mg canagliflozin only during this unequal follow-up period with OR: 1.35, 95% CI: 1.06-1.72; P = 0.01, but it was not significantly different when trials with similar follow-up periods were analyzed. Conclusion 300 mg canagliflozin was not associated with significantly higher adverse events compared to 100 mg canagliflozin in those patients who were treated for T2DM. However, because this result was partly affected by other anti-diabetic medications which were included in the treatment regimen, further studies based on patients who were treated strictly on canagliflozin monotherapy should be recommended to completely solve this issue.